Pengembangan Pariwisata Kawasan Gede Bage Berbasis Ekowisata - Afriza, Lia; Riyanti, Anti; Indrianty, Septy (Universitas Pendidikan Indonesia, 2017)
Bandung provides a variety of tourist attractions, such as culinary arts, theme parks, and shopping destination. The city is developed into a city of technology or technopolis which is located in the southern part region, called Gede Bage. Thus, to maintain the natural environment in the technology-based development area, the city also encouraging eco-tourism activities. Hence, the purpose of this study is to identify the concept of eco-tourism in accommodating the impact of technopolis development. The approach adopted in this study was comprehensive policy analysis approach that examined the norms imposed in developing the city and tourism. The norms consist of regulation, strategies, planning documents, law and other related policies. The results show that the existing facilities at technopolis area are potentials to be developed as eco-tourism attraction. Furthermore, competent human resources have played as an important role to succeed the Bandung Technopolis area as eco tourism attraction.